Desain Ruang Bimbingan dan Konseling (BK) di Pendidikan Nonformal - Ramadhania, Salsa Billa Ashary; Sulusyawati, Heni; Amelia Putri, Winda; Yuningsih, Kartika (Jurnal Bimbingan dan Konseling Pandohop, 2026)
This study aims to examine the concept and implementation of Guidance and Counseling (BK) room design in non-formal educational institutions. The background of this research is based on the importance of creating a safe, comfortable, and effective counseling process. In the context of non-formal education, many institutions still lack adequate BK facilities, particularly in terms of space and supporting resources. This study employs a qualitative descriptive method using a literature review approach to analyze various theories, research findings, and expert perspectives related to counseling room design, environmental psychology, and the principles of privacy and comfort in counseling services. The findings indicate that BK room design has a significant impact on the effectiveness of the counseling process, particularly in fostering a supportive emotional atmosphere, enhancing communication quality, and strengthening the counselor–counselee relationship. The main principles of BK room design include privacy, comfort, flexibility, and alignment with local cultural values. Furthermore, design adaptation in non-formal educational settings can be achieved through the use of modular and portable furniture, simple decorations, and lightweight technology. Consequently, BK room design is not only aesthetically appealing but also psychologically and therapeutically meaningful, which is essential for establishing effective and humane counseling relationships.